Animal hoarding cases in England: Implications for public health services - Wilkinson, Justine; Schoultz, Mariyana; King, Helen M.; Neave, Nick; Bailey, Catherine (Frontiers in Public Health, 2022)
Hoarding disorder is characterized by an accumulation of possessions due to excessive acquisition of or difficulty discarding possessions, regardless of their actual value and is estimated to affect 2–6% of the population. Animal hoarding, a distinct subset of hoarding disorder, has a significant public health impact on the humans involved, as well as animal welfare. Individuals exhibit self-neglect, apathy, social withdrawal and object hoarding; living within squalid, deteriorated, structurally unsafe and uninhabitable premises, alongside neglected animals. Cases are complex, costly and impact on a range of responding service providers. Effective case management is poorly understood and researched, with published literature in England particularly sparse. Improving understanding of the characteristics of these cases is the first step in informed case management. This research is the first exploration of the characteristics of animal hoarders in England and the areas where cases were located. Information about prosecutions involving large numbers of animals that were reported in the media was systematically obtained. This identified 66 cases between January 2015 and December 2020. Geospatial analysis exploring characteristics of locations where animal hoarding cases are also reported. Findings were broadly consistent with the international literature in that females (64%), those living alone (71%) and those with a mean age of 49 were well represented. Cats (61.5%) and dogs (60%) were the most commonly hoarded species. There was a mean of 44 animals per case and dead or animals requiring euthanasia found in 53% of cases. Key characteristics of the areas where cases were found highlight urban, densely populated, and high levels of deprivation being the most represented. Evidence of recidivism was evident in 39% of cases, suggesting that prosecution is not an effective rehabilitator. Animal hoarding raises serious implications for Public Health Services, and the lack of current effective case management strategies are discussed.